Characterizing Osteochondral Allograft Biomechanics for Optimizing Transplant Success: A Systematic Review - Luk, Josephine; Troyer, Luke; Guess, Trent M.; Teixeiro, Emma; Stannard, James P.; Cook, James L. (The Journal of Knee Surgery, 2023)
Osteochondral allograft (OCA) transplantation has been largely successful in treating symptomatic articular cartilage lesions; however, treatment failures persist. While OCA biomechanics have been consistently cited as mechanisms of treatment failure, the relationships among mechanical and biological variables that contribute to success after OCA transplantation have yet to be fully characterized. The purpose of this systematic review was to synthesize the clinically relevant peer-reviewed evidence targeting the biomechanics of OCAs and the impact on graft integration and functional survival toward developing and implementing strategies for improving patient outcomes. The Cochrane Central Register of Controlled Trials, the Cochrane Database of Systematic Reviews, MEDLINE, PubMed, Cumulative Index to Nursing and Allied Health (CINAHL), Google Scholar, and EMBASE were searched to identify articles for systematic review. This review of relevant peer-reviewed literature provided evidence that the biomechanics related to OCA transplantation in the knee have direct and indirect effects on functional graft survival and patient outcomes. The evidence suggests that biomechanical variables can be optimized further to enhance benefits and mitigate detrimental effects. Each of these modifiable variables should be considered regarding indications, patient selection criteria, graft preservation methodology, graft preparation, transplantation, fixation techniques, and prescribed postoperative restriction and rehabilitation protocols. Criteria, methods, techniques, and protocols should target OCA quality (chondrocyte viability, extracellular matrix integrity, material properties), favorable patient and joint characteristics, rigid fixation with protected loading, and innovative ways to foster rapid and complete OCA cartilage and bone integration to optimize outcomes for OCA transplant patients.
Keywords: osteochondral allograft; healing biomechanics; cartilage; transplantation